PENGARUH METODE PEMBELAJARAN DAN KECERDASAN NATURALIS TERHADAP PENGETAHUAN SISWA TENTANG KONSEP EKOSISTEM (Eksperimen di Sekolah Dasar Negeri 4 Tangerang) - Husin, Azizah (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2012)
The objectives of this research are to determine the effect of teaching methods and naturalistic intelligence toward knowledge of student’s ecosystem concept. The research was accomplished at public elementry school and applied treatment by level 2x2 design. The samples of the research are the students of grade VI sub district Ciledug Tangerang with 80 samples taken by cluster random sampling. The result of this research showed: (1) Knowledge of the student’s ecosystem concept who are taught through experiential learning method higher than problem solving method, (2) There is interaction effect between teaching method and naturalistic intelligence toward knowledge of student’s ecosystem concept. (3) The student with high naturalistic intelligence, knowledge of student’s ecosystem concept between student who are thaught through problem solving method higher than experiential learning method , (4) The student with low naturalistic intelligence, knowledge of student’s ecosystem concept between student who are thaught through experiential learning method higher than problem solving method. Therefore, for achievement better result in improving student’s ecosystem concept, applying experiential learning method suggested.